The evidence in the sanctioning administrative Law in Perú and Spain - Magide Herrero, Mariano (2020)
The purpose of this article is to analyze the main aspects related to the regulation of the evidence in the Peruvian and Spanish sanctioning administrative law, with special emphasis on the regulation and use of the evidence for indications. For this, the authors will review the applicable legislation in both legal systems, as well as various judicial and administrative resolutions issued with respect to the evidence, and, in particular, in relation to the validity criteria required for the evidence for indications in the sanctioning administrative field.